Towards the new paradigm of corporate organized crime in Peru: the legal entity as an institutional guarantee against asocial institutions - Palomino Campomanes, Dereck Patrick (2024)
This article aims to establish restrictive criteria on the corporate criminal catalog included in Law 30424 to provide valid selection criteria based on politicalcriminal and dogmatic foundations that determine a coherent systematic in the criminal liability regime of legal entities. In particular, the plausibility of organized terrorist crime applied to companies’ criminal liability will be delved into as an example for a restrictive analysis of the selection criteria.To verify the viability of the restrictive parameters, the analysis will focus on a three-coordinate reference system (perpetrator-act-victim), which will be complemented with the substantive elements of the legal entities imputation system to establish regulatory limits. Finally, a normative conception of the institutional dimension of the legal entity will be proposed, demonstrating its capacity to perform against asocial institutions, in other words, institutions that operate beyond the rules.